The yin and yang of idiopathic pulmonary fibrosis - Kreuter, Michael; Cottin, Vincent (The European respiratory journal, 2017)
Tweetable abstract ERSpublications click to tweetIPF registries and clinical trial data complement each other http://ow.ly/Te9C307KonP
Gesehen am 06.06.2018